Stress and poverty a cross-disciplinary investigation of stress in cells, individuals, and society - Breitenbach, Michael 1943-2024; Kapferer, Elisabeth 1977-; Sedmak, Clemens 1971- (Springer, 2021)
The word stress is everywhere and highly overused. Everyone is stressed, it seems, all the time. Looking into the meaning of stress in the natural science and the humanities, this book explores cellular stress as cause of and in correlation with what humans experience as stress. When do we psychologically feel stress and when do we show physiological evidence of stress in our brain? Stress is a deviation from what feels normal and healthy. It can be created by social or economic factors and become chronic, which has substantial impacts on the individual and society as a whole. Focusing on poverty as one chronic inducer of stress, this book explores how the lack of pressure-free time, the hardships and unpredictability of everyday life and a general lack of protection lead to destructive toxic stress. This pressure affects cognitive and social functioning, brain development during childhood and may also result in premature aging. How can the sciences inform our understanding of and our response to stress? What can be done about toxic stress both on a personal level and in terms of structures and policies? The book is written for anyone interested in stress, its causes and consequences, and its relationship to poverty.
Keywords: Cell biology; Social structure; Social inequality; Human physiology; Health psychology; Medical biochemistry; Health promotion